2011
DOI: 10.4049/jimmunol.1003599
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Transient Activation of γδ T Cells to IFN-γ Production, NK Cell-Like Killing, and Antigen Processing during Acute Virus Infection

Abstract: γδ T cells are the majority peripheral blood T cells in young cattle. The role of γδ T cells in innate responses against infection with foot-and-mouth disease virus was analyzed on consecutive 5 d following infection. Before infection, bovine WC1+ γδ T cells expressed a nonactivated phenotype relative to CD62L, CD45RO, and CD25 expression and did not produce IFN-γ ex vivo. Additionally, CD335 expression was lacking and no spontaneous target cell lysis could be detected in vitro, although perforin was detectabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
48
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 46 publications
2
48
1
Order By: Relevance
“…CD25 expression substantially increased on both WC1.1 + and WC1.2 + cells after only 1 day of culture with Con A relative to that on cells cultured with medium. Furthermore, the diagrams presented in Toka et al (2011) show that about 20% of WC1 + lymphocytes collected from healthy 3-5-month-old calves constitutively expressed CD25, whereas the value was several times higher 2-3 days after infection of the animals with the O1 Manisa strain of FMDV. The study conducted by Sanbulte and Roth (2002) + cells in the same manner, the percentage of cells which produce only IFN-γ, only IL-10 or which co-produce IFN-γ and IL-10 is 32.83%, 52.81% and 14.36%, respectively.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…CD25 expression substantially increased on both WC1.1 + and WC1.2 + cells after only 1 day of culture with Con A relative to that on cells cultured with medium. Furthermore, the diagrams presented in Toka et al (2011) show that about 20% of WC1 + lymphocytes collected from healthy 3-5-month-old calves constitutively expressed CD25, whereas the value was several times higher 2-3 days after infection of the animals with the O1 Manisa strain of FMDV. The study conducted by Sanbulte and Roth (2002) + cells in the same manner, the percentage of cells which produce only IFN-γ, only IL-10 or which co-produce IFN-γ and IL-10 is 32.83%, 52.81% and 14.36%, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…The WC1.1 + cells appeared to be the main producers of IFN-γ, whereas the WC1.2 + cells have been reported to proliferate in response to stimulation with mitogens (Rogers et al 2005a, b). Although the two populations can be distinguished, there is too little information to conclude that they differ functionally (Toka et al 2011). Several investigations have been designed specifically to determine the function of bovine γδ T cells, and particularly cells expressing WC1, in immune responses against various pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…γδ + T cells are found in large proportions in cattle; they may comprise up to 60% of circulating lymphocytes in calves and decrease in adults up to 8-18% (Baldwin and Telfer, 2015). They can recognize antigens in their native form without MHC class I or II presentation (Baldwin and Telfer, 2015) and they have been shown to mount cytotoxic, cytokines and proliferative responses in several viral infections in cattle (Amadori et al, 1995;Bukowski et al, 1994;Silflow et al, 2005;Toka et al, 2011). γδ + T lymphocytes play a crucial role against intracellular pathogens, linking innate and specific immune responses (Baldwin and Telfer, 2015;Pollock and Welsh, 2002), and even a subpopulation of them can act as immune regulatory cells (Hoek et al, 2009).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, young cattle have high levels of γδ T cells, which are found in blood circulation and can respond to autologous molecules and recognize non-peptide antigens [18,23,25,30,31]. It has also been reported that γδ T cells can act as antigen-presenting cells; but, the induction sites for profes- sional antigen-presenting γδ T cells have not been fully determined in vivo [6,12,31,39]. We speculate that γδ T cells, which are distributed in the lymphatic cord along the sinus of HN, have a potential for antigen presenting cell (manuscript in preparation).…”
Section: Discussionmentioning
confidence: 99%